STUDI BANDING PENGGUNAAN GIS UNTUK PENGEMBANGAN PARIWISATA BERKELANJUTAN DAN INVENTARISASI LAHAN KRITIS: PENDEKATAN DALAM PERENCANAAN WILAYAH DAN KOTA - Sirait, Tony; Lubis, Ruri Prihatini; Hidayat, Wahyu (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Geographic Information Systems (GIS) play a significant role in regional and urban planning, facilitating the management of spatial data for better decision-making. This study compares two cases: the utilization of GIS in tourism development in Surat Thani Province and Bogor Regency, and the use of GIS for critical land inventory in North Kolaka Regency. The first study highlights the capability of GIS in supporting sustainable development through ecotourism, while the second study focuses on land criticality analysis using remote sensing data and GIS for land-use planning. The comparison results indicate that GIS can support strategic planning at various scales, with a flexible approach tailored to specific needs. This study recommends integrating GIS methods for more holistic regional and urban planning, combining strategic spatial analysis and local data to enhance data-driven decision-making.